The generation of granule cells during the development and evolution of the cerebellum. Issue 7 (10th June 2019) - Iulianella, Angelo; Wingate, Richard J.; Moens, Cecilia B.; Capaldo, Emily
Abstract: The cerebellum coordinates vestibular input into the hindbrain to control balance and movement, and its anatomical complexity is increasingly viewed as a high‐throughput processing center for sensory and cognitive functions. Cerebellum development however is relatively simple, and arises from a specialized structure in the anterior hindbrain called the rhombic lip, which along with the ventricular zone of the rostral‐most dorsal hindbrain region, give rise to the distinct cell types that constitute the cerebellum. Granule cells, being the most numerous cell types, arise from the rhombic lip and form a dense and distinct layer of the cerebellar cortex. In this short review, we describe the various strategies used by amniotes and anamniotes to generate and diversify granule cell types during cerebellar development. Key Findings: Strategies used by vertebrates to generate cerebellar granule cells. Role of Atoh1, Neurod1, and Cux2 in the patterning and migration of granule cell precursors.